1999
DOI: 10.1074/jbc.274.48.34059
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Glucose-responsive Human Insulin-secreting Cell Line from Islets of Langerhans Isolated from a Patient with Persistent Hyperinsulinemic Hypoglycemia of Infancy

Abstract: Persistent hyperinsulinemic hypoglycemia of infancy (PHHI) is a neonatal disease characterized by dysregulation of insulin secretion accompanied by profound hypoglycemia. We have discovered that islet cells, isolated from the pancreas of a PHHI patient, proliferate in culture while maintaining a beta celllike phenotype. The PHHI-derived cell line (NES2Y) exhibits insulin secretory characteristics typical of islet cells derived from these patients, i.e. they have no K ATP channel activity and as a consequence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 38 publications
(41 reference statements)
2
65
0
2
Order By: Relevance
“…Activation of pdx-1 seems to be induced by nutrient stimulation (21) and, as shown by Macfarlane et al (22), high glucose induces nuclear translocation of pdx-1 in rat islets by a mechanism governed by SAPK2. Furthermore, pdx-1 expression has been shown to be impaired in a patient with persistent hyperinsulinemic hypoglycemia of infancy (23). We also found that the translocation of GLUT2 to the plasma membrane was compromised in mice fed the high-fat diet, which would perturb the islets' capacity to adequately respond to glucose.…”
Section: Discussionmentioning
confidence: 63%
“…Activation of pdx-1 seems to be induced by nutrient stimulation (21) and, as shown by Macfarlane et al (22), high glucose induces nuclear translocation of pdx-1 in rat islets by a mechanism governed by SAPK2. Furthermore, pdx-1 expression has been shown to be impaired in a patient with persistent hyperinsulinemic hypoglycemia of infancy (23). We also found that the translocation of GLUT2 to the plasma membrane was compromised in mice fed the high-fat diet, which would perturb the islets' capacity to adequately respond to glucose.…”
Section: Discussionmentioning
confidence: 63%
“…In the least severe forms of the disease, there may be a slower onset of hyperinsulinemia, and it may be chronically treatable without progression to beta cell failure. Importantly, although a complete lack of K ATP activity has been reported in human PHHI beta cells (34)(35)(36), active K ATP channels have been observed in other patient samples (36,37), consistent with the reduced channel activity that is the result of many disease mutations when they are expressed in recombinant systems (3, 38, 39 ‡). ‡Cosgrove, K. E., Gonzalez, A. M., Lee, A. T., Barnes, P. J., Hussaim, K., Aynsley-Green, A., Lindley, K. J., Pirotte, B., Lebrun We are very grateful to Dr. Stan Misler for use of his Ca 2ϩ imaging facility and for valuable discussions during the course of this work.…”
Section: Normal Islet Morphology Is Maintained In Kir62[aaa]mentioning
confidence: 87%
“…Other investigators have attempted to immortalize fetal or adult human beta cells or non-pancreatic cells using transfection with oncogenes and pancreatic endocrine developmental markers (15,16). The human Persistant Hyperinsulinemic Hypoglycemia of Infancy (PHHI)-derived pancreatic beta cell line, NES2Y, has also been reported to exhibit glucosestimulated insulin secretion after successful transfection to repair defects in expression of K-ATP channel and PDX-1 genes (17). Blox5 is an immortalized cell line produced from a purified population of human beta cells by infection with retroviral vectors expressing the SV40 T antigen, H-ras val12 , and hTERT oncogenes (18).…”
mentioning
confidence: 99%